2010
DOI: 10.4319/lo.2010.55.6.2503
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration and zooplankton lunar cycles: Could we be missing a major component of the biological pump?

Abstract: The plankton outburst during the so-called late winter bloom in subtropical waters was studied in relation to lunar illumination in the Canary Island waters. Nutrient enrichment by mixing and dust deposition promoted a bloom of phyto-and zooplankton. Mesozooplankton biomass increased as the winter mixing progressed but peaked in every full moon and decreased thereafter because of the effect of predation by interzonal diel vertical migrants (DVMs). The pattern was similar to the one described in lakes due to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…Additional environmental variability is provided by the influence of diazotrophy (atmospheric nitrogen fixation) in the subtropical region, generally more important in the western waters but occasionally affecting also waters near Canary Islands [26][27][28][29][30]. Zooplankton composition and biomass in this region reflect the productivity of the surface waters (for example, References [21,25]) and previous studies on the vertical migrations of zooplankton [12,25] and mesopelagic fish [31] showed a measurable impact of these movements on carbon fluxes and export to deep ocean layers. Stable isotopes revealed that some of the most abundant mesopelagic fish (as myctophids) greatly depend on zooplankton [32], while copepods (one of the most abundant zooplankton taxa) showed a marked increase in heavy nitrogen isotopes with depth [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional environmental variability is provided by the influence of diazotrophy (atmospheric nitrogen fixation) in the subtropical region, generally more important in the western waters but occasionally affecting also waters near Canary Islands [26][27][28][29][30]. Zooplankton composition and biomass in this region reflect the productivity of the surface waters (for example, References [21,25]) and previous studies on the vertical migrations of zooplankton [12,25] and mesopelagic fish [31] showed a measurable impact of these movements on carbon fluxes and export to deep ocean layers. Stable isotopes revealed that some of the most abundant mesopelagic fish (as myctophids) greatly depend on zooplankton [32], while copepods (one of the most abundant zooplankton taxa) showed a marked increase in heavy nitrogen isotopes with depth [21].…”
Section: Introductionmentioning
confidence: 99%
“…Migrating organisms include phyto-and zooplankton [7,8], fish [9,10], cephalopods, seabirds, mammals, and even reptiles [11]. Most migrations have been related to the daily light cycle but also to the lunar [12] and seasonal periods [13]. One of the major drivers of these migrations is food [9].…”
Section: Introductionmentioning
confidence: 99%
“…Mesopelagic (200 to 1000 m depth) fishes are important planktivores and prominent prey for higher trophic levels in all the world's oceans (Gjøsaeter & Kawaguchi 1980, Lam & Pauly 2005 and, because of pronounced diel vertical migrations (DVM), contribute to the biological pump whereby organic material is transported from upper layers down to the waters at depth (Hidaka et al 2001, Hernández-León et al 2010. The current global biomass estimate of mesopelagic fishes, primarily based on catches by micronekton sampling gears prior to 1980, amounts to approximately 1 gigatonne (10 9 t wet weight) (Gjøsaeter & Kawaguchi 1980, Lam & Pauly 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their diel vertical migration (DVM), mesopelagic fish link primary consumers including copepods and zooplankton to higher predators including large pelagic fish, benthic fish, and marine mammals (Choy et al, 2012;Collins et al, 2012;Olivar et al, 2012). They play an important role in ocean food webs (Cherel et al, 2010;Kaartvedt et al, 2012), and their DVM behavior makes a significant contribution to the transfer of organic matter from the upper productive layer to deeper layers (Radchenko 2007; Hernández- León et al, 2010;Dypvik et al, 2012). However, the huge biomass of these fish is underutilized.…”
Section: Introductionmentioning
confidence: 99%